BEYOND IMAGE AND QUALITY: DUAL MEDIATION OF DESTINATION VALUE AND HISTORICAL TOURIST ENGAGEMENT ON REVISIT INTENTION - Anggraeni, Tuti; Sidik, Az Zahra Ibrahim; Sidik, Adam Maulana (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Yogyakarta tourism faces challenges in maintaining repeat visit s amid fierce competition. Although destination image and quality are recognized as important factors, the mechanisms that drive these two factors toward long-term revisit intention are still not fully understood. A quantitative research method with a survey approach was used to collect data from 145 tourists who had visited Yogyakarta at least twice. Sampling was conducted using purposive sampling, and the data were analyzed using PLS-Structural Equation Modeling (SEM). The results of the measurement model analysis showed that all indicators used were valid and reliable. Meanwhile, structural model analysis revealed that all proposed direct path hypotheses were statistically significant. In absolute terms, the variable with the strongest overall influence in the model was DI, mainly due to its very strong influence (path coefficient of 0.753) on the RI variable, which is often the main dependent variable (outcome variable) in models such as this. However, if we look at how much DQ influences other variables, DQ is an important variable that acts as a “generator” or predictor for several other latent variables (DI, DV, and HTE) with a significant influence. DI has the strongest direct influence on the final variable (RI), while DQ has a strong influence on the mediating variables (DI, DV, HTE) which then influence RI. This study suggests that destination managers should focus on strategies that can create unique value and build emotional engagement among tourists, rather than focusing solely on improving physical quality and promoting image.